2023
DOI: 10.4049/jimmunol.2200897
|View full text |Cite
|
Sign up to set email alerts
|

IL-12 and IL-27 Promote CD39 Expression on CD8+ T Cells and Differentially Regulate the CD39+CD8+ T Cell Phenotype

Abstract: Tumor-specific CD8+ T cells are critical components of antitumor immunity; however, factors that modulate their phenotype and function have not been completely elucidated. Cytokines IL-12 and IL-27 have recognized roles in promoting CD8+ T cells’ effector function and mediated antitumor responses. Tumor-specific CD8+ tumor-infiltrating lymphocytes (TILs) can be identified based on surface expression of CD39, whereas bystander CD8+ TILs do not express this enzyme. It is currently unclear how and why tumor-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Meanwhile, CD4 + T cells could promote the recruitment and activation of CD8 + T cells, macrophages and natural killer (CD57 + ) cells to enhance the antitumor effect. Studies revealed CD39 could serve as a marker for identification of tumor-specific T cells and CD39 + CD8 + , CD39 + CD4 + TILs were found to be beneficial for antitumor activity (26,27). Interestingly, FOXP3 + T cells are usually regarded as suppressive T cells in many cancers except CRC, in which FOXP3 + T cells indicated better prognosis in some studies (12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, CD4 + T cells could promote the recruitment and activation of CD8 + T cells, macrophages and natural killer (CD57 + ) cells to enhance the antitumor effect. Studies revealed CD39 could serve as a marker for identification of tumor-specific T cells and CD39 + CD8 + , CD39 + CD4 + TILs were found to be beneficial for antitumor activity (26,27). Interestingly, FOXP3 + T cells are usually regarded as suppressive T cells in many cancers except CRC, in which FOXP3 + T cells indicated better prognosis in some studies (12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%